Impatiens shamaii sp. nov. (Balsaminaceae)—a new species from Arunachal Pradesh, Eastern Himalaya, India - Singh, Sumit (Phytotaxa, 2025)
A new species Impatiens shamaii from Tawang district of Arunachal Pradesh has been described and illustrated. Although it closely resembles Impatiens albopetala but, differs in number characters like long petiole, inflorescence number of flowers, lanceolate to elliptic leaves, funnel-shaped lower sepal and fusiform capsule.